Using the power of innate immunoprofiling to understand vaccine design, infection, and immunity - Jennifer Connors; Gina Cusimano; Nathan Mege; Kyra Woloszczuk; Emily Konopka; Matthew Bell; David Joyner; Jennifer Marcy; Virginie Tardif; Michele A. Kutzler; Roshell Muir; Elias K. Haddad (Human Vaccines & Immunotherapeutics, 2023)
In the field of immunology, a systems biology approach is crucial to understanding the immune response to infection and vaccination considering the complex interplay between genetic, epigenetic, and environmental factors. Significant progress has been made in understanding the innate immune response, including cell players and critical signaling pathways, but many questions remain unanswered, including how the innate immune response dictates host/pathogen responses and responses to vaccines. To complicate things further, it is becoming increasingly clear that the innate immune response is not a linear pathway but is formed from complex networks and interactions. To further our understanding of the crosstalk and complexities, systems-level analyses and expanded experimental technologies are now needed. In this review, we discuss the most recent immunoprofiling techniques and discuss systems approaches to studying the global innate immune landscape which will inform on the development of personalized medicine and innovative vaccine strategies.